Fertilization and maize yields in a four-year cycle crop rotation under various soil and climatic conditions - Iliyana Gerassimova; Martin NENOV; Tsetska SIMEONOVA; Miladin NAZARKOV; Zdravka PETKOVA (Journal of Central European Agriculture)
Crop rotation is the main factor in reducing losses caused by weeds, diseases, and pests and increasing yields, which has been used little in recent years in intensive agriculture. The study aimed to estimate the influence of two rates of nitrogen-phosphorus mineral fertilization on the yield of maize grown in a four-year cycle crop rotation - under various soil and climatic conditions. During the period 2020-2023 field experiments on two different soil types with their specific characteristics have been carried out - Leached Smolnitsa (Haplic Vertisol) and Alluvial-meadow soil (Eutric Fluvisol) in the experimental station of ISSAP "N. Poushkarov", the town of Bozhurishte (Sofia region) and the village of Tsalapitsa (Plovdiv region). The maize was included in the structure of a four-year cycle crop rotation: 1) maize, 2) wheat, 3) maize and 4) wheat. A test crop was a mid-early maize hybrid "P-8834" by “Pioneer” from group 310, according to FAO. Two factors from the general agrotechnical complex were studied: soil-climatic conditions and rates of mineral fertilization. It was established that the studied fertilizer rates were an important factor in increasing the yields, which determined more than 57.82% and 97% of the variation of the data, respectively for Leached Smolnitsa and Alluvial-meadow soil. With the increase in the rate of nitrogen and phosphorus fertilizers, the productivity of maize grown on both soil types also increases. As a result of the use of nitrogen-phosphorus mineral fertilization, more than twice as high yields were obtained, compared to the non-fertile variants. The influence of the soil-climate conditions (precipitation and temperature conditions) during this period was also analyzed. It was established that they are a significant factor which has a strong influence on the obtained high (good) yields of non-irrigated maize cultivated in the field of Bozhurishte.